Natural Product Testing: Selecting in vivo Anticancer Assay Model : In vivo anticancer assay model - Saad, Dr. Norazalina; Chia, Suet Lin; Che Abdullah , Che Azurahanim; Sulaiman, Fadzil (Journal of Tropical Life Science, 2024)
Phytochemicals and other natural products have been suggested to be effective adjuvants to conventional therapy to reduce potential side effects that arise from cancer treatments. Various natural compounds and synthetic analogues have been studied for their potential anti-cancer properties in the last decade. Prior to administering them to patients in a clinical setting, drug development necessitates a sequence of preclinical testing, beginning with in vitro and progressing to in vivo studies. While numerous drugs and plant extracts were reported to be active in vitro, only several of them had reproducible activity at the tested doses in vivo. Furthermore, breakthroughs in manipulating gene editing have aided scientists in accurately replicating human diseases in animal models. Therefore, during drug development, in vivo studies are of tremendous help in evaluating a drug candidate's safety, toxicity, and efficacy in complex physiological and biochemical states. Hence, for this purpose, it is crucial to apply and select the animal model that is the most suitable to represent the studied disease or biological process. The current review summarizes various animal models that have been considered for in vivo testing, their advantages and disadvantages, and the experimental guidelines for conducting animal studies.